Surfactant treatment and incidence of intraventricular haemorrhage in severe respiratory distress syndrome. Issue 1 (January 1988) - McCord, F B; Curstedt, T; Halliday, H L; McClure, G; Reid, M M; Robertson, B
Abstract : As part of a multicentre study of porcine surfactant administration in respiratory distress syndrome, 29 babies weighing 2000 g or less were studied in the neonatal intensive care unit of the Royal Maternity Hospital, Belfast. Fourteen babies of a mean gestational age of 28.1 weeks were randomly allocated to the treatment group (200 mg/kg phospholipid given intratracheally) and 15 babies of a mean gestational age of 28.7 weeks formed the control group. All babies had severe respiratory distress syndrome (oxygen requirement over 60%, mechanical ventilation, and age 15 hours or less). Almost immediate improvement in oxygenation was seen in the treated group so that oxygen concentrations could be reduced and remained significantly lower than those of control babies for the first seven days of life. Alveolar-arterial oxygen gradients were also significantly different for the first five days after treatment. More babies in the treatment group survived (79% v 40%) but the difference was not significant. The incidence of pneumothorax and of intraventricular haemorrhage, however, was significantly lower in treated babies compared with controls. For babies weighing less than 1200 g the risk of developing or extending intraventricular haemorrhage after entry to the study was also reduced in the treatment group (29% v 100%).